2012
DOI: 10.1155/2012/407601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Male Obesity on Semen Quality and Serum Sex Hormones

Abstract: Introduction. To investigate the association of high Body Mass Index (BMI) with semen parameters and reproductive hormones in men of reproductive age. Setting. The Saudi Center for Assisted Reproduction. Method. This study was conducted during the period from February 2009 to February 2011. Subjects were exposed through medical history evaluation as well as physical examination. BMI was calculated. Two semen samples about 1 week apart were taken from each participant by masturbation after 2–5 days of abstinenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
4
22
0
3
Order By: Relevance
“…This study did not reveal any relationship between BMI and any of semen parameters of the studied population. The results of this study were generally in accordance with some previous studies [8] [9].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study did not reveal any relationship between BMI and any of semen parameters of the studied population. The results of this study were generally in accordance with some previous studies [8] [9].…”
Section: Discussionsupporting
confidence: 93%
“…Obese men exhibit poor sperm quality, reduced androgen levels, elevated estradiol levels and reduced inhibin B correlating with the degree of obesity [6] [7]. On the other hand, some studies reported that there was no significant correlation between body mass index (BMI) and semen or hormonal parameters [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Más recientemente, McDonald et al 19 han demostrado que la disrupción endocrina que presentan pacientes con sobrepeso u obesidad impacta negativamente en su calidad seminal. Sin embargo, al revisar la literatura no existe un consenso total sobre este asunto, ya que otros autores no han encontrado una correlación estadísticamente significativa entre dichas variables 20 . Por consiguiente, futuros estudios en esta línea de trabajo son aún necesarios Por otra parte, la mala calidad seminal que hemos observado en pacientes con síndrome metabólico podría explicarse, al menos en parte, por los mayores niveles de daño oxidativo observados en el plasma seminal de los participantes en nuestro estudio.…”
Section: Discussionunclassified
“…Resultados similares fueron publicados anteriormente por Hammiche et al 17 confirmando el impacto negativo de la obesidad abdominal en la calidad seminal. Por el contrario, Eskandar et al 20 no encontraron correlaciones significativas entre el índice de masa corporal (IMC) y marcadores de calidad seminal. Sin embargo estos mismos autores no estudiaron ningún índice de distribución de masa grasa abdominal (p. ej.…”
Section: Discussionunclassified
See 1 more Smart Citation